Está en la página 1de 2

Ejercicio.

9
𝑦 ′ = 𝑎 𝑥+𝑦
𝑑𝑦
= 𝑎𝑦 . 𝑎𝑥
𝑑𝑥
𝑑𝑦
= 𝑎 𝑥 . 𝑑𝑥
𝑎𝑦
𝑑𝑦
∫ = ∫ 𝑎 𝑥 . 𝑑𝑥
𝑎𝑦

∫ 𝑎−𝑦 . 𝑑𝑦 = ∫ 𝑎 𝑥 . 𝑑𝑥

− ∫(−). 𝑎−𝑦 . 𝑑𝑦 = ∫ 𝑎 𝑥 . 𝑑𝑥

𝑎 −𝑦 𝑎𝑥
− = +𝑐
ln 𝑎 ln 𝑎
𝑎−𝑦 𝑎𝑥
= − −𝑐
ln 𝑎 ln 𝑎
𝑎−𝑦 = −𝑎 𝑥 − ln 𝑎 . 𝑐
−𝑦 = log 𝑎 (−𝑎 𝑥 − ln 𝑎 . 𝑐)
𝑦 = − log 𝑎 (𝑐 − 𝑎 𝑥 )
1
𝑦 = log 𝑎 ( )
𝑐 − 𝑎𝑥
Ejercicio.10

−𝟐𝒙(𝟏 + 𝒆𝒚 )𝒅𝒙 + 𝒆𝒚 (𝟏 + 𝒙𝟐 )𝒅𝒚 = 𝟎


𝑒 𝑦 (1 + 𝑥 2 )𝑑𝑦 = 2𝑥(1 + 𝑒 𝑦 )𝑑𝑥
𝑒𝑦 2𝑥
∫ . 𝑑𝑦 = ∫ . 𝑑𝑥
1 + 𝑒𝑦 1 + 𝑥2

1 2
Integrando 1 Integrando 2
𝑒𝑦 2𝑥
∫ . 𝑑𝑦 ∫ . 𝑑𝑥
1 + 𝑒𝑦 1 + 𝑥2
1 + 𝑒𝑦 = 𝑣 1 + 𝑥2 = 𝑣
𝑒 𝑦 . 𝑑𝑦 = 𝑑𝑣 2𝑥. 𝑑𝑥 = 𝑑𝑣
𝑑𝑣 𝑑𝑣
𝑑𝑦 = 𝑑𝑥 =
𝑒𝑦 2𝑥
𝑒 𝑦 𝑑𝑣 2𝑥 𝑑𝑣
∫ . ∫ .
𝑣 𝑒𝑦 𝑣 2𝑥

∫ 𝑣 −1 . 𝑑𝑣 ∫ 𝑣 −1 . 𝑑𝑣

ln(𝑣) + 𝑐1 ln(𝑣) + 𝑐2
ln(1 + 𝑒 𝑦 ) + 𝑐1 ln(1 + 𝑥 2 ) + 𝑐2
Sustituyendo

ln(1 + 𝑒 𝑦 ) = ln(1 + 𝑥 2 ) + 𝑐
2 )+𝑐
1 + 𝑒 𝑦 = 𝑒 ln(1+𝑥
2 )+𝑐
𝑒 𝑦 = 𝑒 ln(1+𝑥 −1
2 )+𝑐
𝑦 = ln(𝑒 ln(1+𝑥